Exploring the Absence of Science Clubs in Rural Schools: Challenges and Opportunities - Ntuli, Thuli; Chuene, Mahlako Valentia; Munasi, Khathutshelo Ronald; Masuvhe, Lawrence; Broadhurst, Jodi-Leigh (Journal of Innovative Science Education, 2025)
Science clubs enhance learner engagement, promote scientific literacy, and support inquiry-based learning beyond the classroom. However, their presence remains limited in rural schools. This study explored factors influencing the absence and potential establishment of science clubs in selected rural schools within the Vhembe East District, Limpopo Province. Using a qualitative approach framed by the Communities of Practice (CoP) theory, data was collected from 19 Science teachers across seven rural schools in Vhembe East District through focus group interviews and questionnaires. The findings reveal limited awareness of science clubs, lack of resources, insufficient teacher training, minimal administrative support, and geographic challenges as key barriers. Despite these constraints, teachers acknowledged the value of science clubs in developing learners’ critical thinking and interest in science. The study recommends teacher training, increased resource allocation, improved institutional support, and partnerships with external stakeholders such as universities to ensure the existence of science clubs in rural schools. Adapting science club models to the rural context is essential for sustainability. These insights contribute to understanding the systemic and contextual factors affecting informal science learning and offer guidance for promoting science clubs in under-resourced schools.